CREATIVE CAMP, COWORKING SPACE, AND INNOVATION LABS AS LEARNING RESOURCES FOR STARTUP-ENGAGED STUDENTS - Tafrienda, Ulfa Nabila; Wahyono, Sugeng Bayu (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2025)
Abstract: This study explores the role of Creative Camp, Coworking Space, and Innovation Labs at Indigo Space Padang as innovative learning resources for student startup activists. The background addresses global challenges in critical learning and the untapped potential of Indonesia’s creative industry. Using a descriptive qualitative approach with a prospective case study, data were collected through observation, in-depth interviews, and documentation involving 12 student users of the facilities. Key findings reveal: (1) Creative spaces foster collaborative environments through comprehensive facilities, training programs (workshops, mentoring), and professional networks; (2) Enhanced technical competencies (technology, prototyping) and non-technical skills (business management, communication), alongside access to startup funding; (3) Driving factors include free facilities, structured programs beyond campus curricula, and an experiential learning-based ecosystem. The study concludes that integrating these three spaces successfully bridges academic theory with industrial practice, strengthening students’ career readiness in the digital era. The collaborative model can serve as a reference for universities and policymakers to support digital economic growth by empowering the younger generation through innovative learning ecosystems.